PERAN PEMERINTAH DESA DALAM PEMBERDAYAAN KELOMPOK INFORMASI MASYARAKAT - Roro Merry Chornelia; Noora Fithriana; Abd. Rohman (REFORMASI, 2022)
Empowerment can be said as a process of building a community through capacity building and behavior change in an organization. The purposes of this research are to determine the role of rural government to empower the information group of societies in the village of Tlekung, Bumiaji, Batu; its supporting and inhibiting factors. This research used a qualitative approach to obtain the primary and secondary data. The research results determined that the Rural Government of Tlekung plays the role successfully so the group can inform many pieces of information in Tlekung by the media. To conduct the job, the Rural Government of Tlekung also gives incentives to the group and controls its activities. The supporting factor of the role of the Rural Government of Tlekung for empowering the group is a good communication style; meanwhile, the inhibiting factor is a fund that lacks to buy some media tools. AbstrakPemberdayaan dapat dikatakan sebagai suatu proses membangun masyarakat melalui pengembangan kemampuan dan perubahan perilakunya dalam suatu organisasi. Tujuan dilakukannya penelitian ini adalah untuk mengetahui peran pemerintah desa dalam pemberdayaan kelompok informasi masyarakat di Desa Tlekung, Kecamatan Bumiaji, Kota Batu, faktor pendukung dan penghambatnya. Penelitian ini menggunakan pendekatan kualitatif untuk memperoleh data primer dan sekunder. Hasil penelitian menunjukkan bahwa Pemerintah Desa Tlekung berhasil berperan dalam pemberdayaan KIM sehingga KIM dapat memberitahukan hal-hal yang sedang dan akan dilaksanakan di Desa Tlekung melalui media-media informasi. Dalam menjalankan perannya, Pemerintah Desa Tlekung juga memberikan insentif kepada KIM dan mengontrol kegiatan KIM. Faktor pendukung peran Pemerintah Desa Tlekung dalam pemberdayaan KIM adalah pola komunikasi yang baik, sedangkan faktor penghambatnya ialah kurangnya dana untuk membelikan peralatan media.